2019
DOI: 10.1038/s41567-019-0598-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional dynamics of two coupled biological oscillators

Abstract: The circadian clock and the cell cycle are two biological oscillatory processes that coexist within individual cells. These two oscillators were found to interact, which can lead to their synchronization. Here, we develop a method to identify a low-dimensional stochastic model of the coupled system directly from time-lapse imaging in single cells. In particular, we infer the coupling and non-linear dynamics of the two oscillators from thousands of mouse and human single-cell fluorescence microscopy traces. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Such coupling between the circadian clock and cell cycle has been studied extensively, both experimentally as well as theoretically (e.g. [ 77 , 78 ]). Here, we use the fact that the expression of the Wee1 kinase is not only affected by DNA damage but also tightly regulated by the Clock-Bmal1 transcription factor complex, a master regulator of the circadian clock ( Fig 8G ) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such coupling between the circadian clock and cell cycle has been studied extensively, both experimentally as well as theoretically (e.g. [ 77 , 78 ]). Here, we use the fact that the expression of the Wee1 kinase is not only affected by DNA damage but also tightly regulated by the Clock-Bmal1 transcription factor complex, a master regulator of the circadian clock ( Fig 8G ) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that the unidirectional coupling between circadian clock and cell cycle as discussed here, merely functions as a conceptual example of our phenomenological modeling approach. Indeed, in reality, the situation is much more complex, as coupling happens in a bidirectional manner [ 77 , 78 ] and also the circadian clock itself includes bistable switches [ 82 ]. Nevertheless, as with the other examples discussed, certain key aspects of the system’s dynamical behavior can be described using the approach proposed here.…”
Section: Resultsmentioning
confidence: 99%
“…The short answer is a surprising yes . For instance, our discussion on the coupling between circadian clock and cell cycle has focused mostly on their 1:1 phase-locking, yet a recent study has experimentally demonstrated that both 1:1 and 1:2 phase-locking ratios can mutually exist even among the same population of cells ( Droin et al, 2019 ). In other words, cells can couple every ~24 hr of the circadian turn to either one (1:1) or half (1:2) a division cycle.…”
Section: The Logic and Potential Evolutionary Origins Of Autonomous Clocksmentioning
confidence: 99%
“…The fact that circadian time captures only a low contribution to total mRNA variability may be surprising given that clear circadian oscillations of a single‐cell reporter ( Rev‐Erbα ‐YFP) are observed in the same NIH 3T3 cells (Nagoshi et al , 2004; Bieler et al , 2014) and in human U2OS cells (Droin et al , 2019). It should be noted that the reporter used in these cells is probably present in many copies, since the cells are typically selected for high signals.…”
Section: Discussionmentioning
confidence: 99%